PENGARUH DANA PIHAK KETIGA TERHADAP LABA OPERASI DENGAN FASILITAS BANK - Della Elvitasari; Ibram Pinondang Dalimunthe (Jurnal Renaissance, 2019)
The purpose of this study is to empirically examine Indonesian banks with regard to the third party funds effect on operating income with banking facilities as a moderating variable. This study uses independent variables is third party funds, the dependent variable is operating income. This study also uses banking facilities as a moderating variable.The population studied in this study consists of Sharia commercial banks in Indonesia registered with the Financial Services Authority, which has 13 banks. The sample used is the annual publication of 11 financial statements of Islamic commercial banks from 2014 to 2016. The data analysis methods used are moderate regression analysis (MRA). The results of this study indicate that third party funds has a significant impact on operating income and that bank facilities strengthen the relationship between third party funds and operating profit.Keywords: Third Party Funds, Bank Facility, Operating Profit